Marka Mikrosatelit sebagai Alternatif Uji BUSS dalam Perlindungan Varietas Tanamam Padi - Sugiono Moeljopawiro (Buletin Plasma Nutfah, 2010)
This study was conducted at theIndonesian Center for Agricultural Biotechnology and GeneticResources Research and Development to seek the feasibility ofusing SSR markers for DUS testing in rice variety. Releasedvariety Fatmawati together with seven other reference varietieswere analyzed using genetic analyzer for their variability, tenSSR markers were used. Hundred and twenty five alleleslocated on chromosomes 1, 2, 5, 6, 7, 10, and 11 were detectedin eight varieties studied, where the number of alleles rangingfrom 6 (BPC) to 33 (Fatmawati), with the predominantmarkers such as RM11 on Fatmawati, Maros, Barumun,Gilirang, and Memberamo varieties, RM237 on Cisadane andBP630 varieties, and RM133 and RM287 markers on BPCvariety. The genetic distance-based results in the unrootedneighbor-joining tree revealed that the eight varieties as well astheir populations clustered separately. Genetic variabilitywithin each variety indicated that these varieties were still inhigher degree of heterogeneity. This demonstrated the powerof SSR marker in differentiating varieties as well as populationwithin variety, which, therefore, SSR marker could berecommended in plant variety protection.